Down-regulation of Sirtuin 1 gene expression correlated with higher atherogenic fatty acid level in the liver of male mice offspring born from high fat-fed mothers - Koohdani, Fariba; Seyed Dorraji, Mir Saeed; Gharacheh, Sara; Hosseini, Elham; Mousavi, Seyedeh Neda (Progress in Nutrition, 2023)
Background: Maternal diet can alter metabolism of offspring through changes in Sirtuin 1 (SIRT1) expression, as a metabolic sensor. However, its correlation with hepatic fatty acid profile is not clear. Herein, the correlation of SIRT1 expression was assessed with hepatic fatty acid profile in offspring born from isocalorie high fat-fed mothers during gestation and lactation. Methods: C57BL/6 female mice were randomized to AIN93G (CG) and high-fat AIN93G (HFG) diets after insemination. Diets were isocaloric by change in fat and carbohydrate percentages. Protein content was similar. After weaning, all offspring received a CG diet. At the adolescence, liver tissue was extracted for assessing SIRT1 expression and fatty acid profile. Results: Gene and protein of SIRT1 decreased in both sexes born from HFG-fed mothers compared with the controls (p<0.001). In female offspring born from the CG-fed mothers, SIRT1 gene expression correlated with lower linoleic acid (r= -0.98, p=0.002) and higher eicosapentaenoic acid (r=0.91, p=0.02) level in the liver. In male offspring born from HFG-fed mothers, down-regulation of SIRT1 gene expression was correlated with higher palmitic (r=0.9, p=0.03), linoleic (r=0.95, p=0.01), arachidonic (r=0.9, p=0.04), acids and cholesterol (r=0.94, p=0.01) in the liver. At the protein level, no significant correlation was observed. Conclusions: Maternal dietary fat and carbohydrate distribution, regardless of calorie intake, effect on hepatic fatty acid profile by SIRT1 gene changes. Atherogenic fatty acids increased in the liver of male mice offspring born from HFG-fed mothers.